Radiosynthesis and preclinical evaluation of [68Ga]Ga-NOTA-folate for PET imaging of folate receptor β-positive macrophages - Moisio O.; Palani S.; Virta J.; Elo P.; Liljenbäck H.; Tolvanen T.; Käkelä M.; Miner M.G.; Herre E.A.; Marjamäki P.; Örd T.; Heinäniemi M.; et al. (Nature Research, 2022)
Folate receptor β (FR-β), a marker expressed on macrophages, is a promising target for imaging of inflammation. Here, we report the radiosynthesis and preclinical evaluation of [68Ga]Ga-NOTA-folate (68Ga-FOL). After determining the affinity of 68Ga-FOL using cells expressing FR-β, we studied atherosclerotic mice with 68Ga-FOL and 18F-FDG PET/CT. In addition, we studied tracer distribution and co-localization with macrophages in aorta cryosections using autoradiography, histology, and immunostaining. The specificity of 68Ga-FOL was assessed in a blocking study with folate glucosamine. As a final step, human radiation doses were extrapolated from rat PET data. We were able to produce 68Ga-FOL with high radiochemical purity and moderate molar activity. Cell binding studies revealed that 68Ga-FOL had 5.1 nM affinity for FR-β. Myocardial uptake of 68Ga-FOL was 20-fold lower than that of 18F-FDG. Autoradiography and immunohistochemistry of the aorta revealed that 68Ga-FOL radioactivity co-localized with Mac-3–positive macrophage-rich atherosclerotic plaques. The plaque-to-healthy vessel wall ratio of 68Ga-FOL was significantly higher than that of 18F-FDG. Blocking studies verified that 68Ga-FOL was specific for FR. Based on estimations from rat data, the human effective dose was 0.0105 mSv/MBq. Together, these findings show that 68Ga-FOL represents a promising new FR-β–targeted tracer for imaging macrophage-associated inflammation.